A note on bounded scale-invariant quantities for the Navier-Stokes equations - Seregin, G (2012)
In this note, we show that if the velocity field v is in L ∞(BMO -1), then all sealed energy quantities are bounded. An interesting consequence is that every axially symmetric solution to the Navier-Stokes equations belonging to L ∞(BMO -1) is smooth. Bibliography: 7 titles. © 2012 Springer Science+Business Media, Inc.